Types of Qiraat Mentioned in the Book of Al-mustadrak Alaa Al-Sahihain - Abdelgelil, Mohamed Fathy Mohamed (International Journal of Psychosocial Rehabilitation, 2020)
Al-Mustadrak Alaa Al-Sahihain is a book in the science of Hadith; however, the author of the book devoted one chapter for Qiraat (readings or recitations of the Quran) and so he contributed to the science of Qiraat. The problem lies in the fact that novice scholars may believe that Qiraat must be drawn from Sahih ‘authentic’ Hadith so that it can be considered acceptable Qiraat. However, this could be a serious mistake as there is a difference in rules of acceptance between the science of Hadith and the science of Qiraat. The purpose of this paper to showcase Qiraat mentioned in the book of Mustadrak. The researcher adopted an analytical approach by tracing Qiraat and prophetic traditions mentioned in the chapter of Qiraat of Al-Mustadrak by classifying them and determining authenticity of the prophetic traditions on these Qiraat. The findings show that Al-Hakim did not place the chapters of the Quran according to the order they appear in the Holly book of the Quran. Moreover, he did not care for dividing Mutawatir Qiraat (narrated by a large number of people) and Shath ‘irregular’ Hadith. It was also found that there are four types of Qiraat in Al-Mustadrak namely, Mutawatir Qiraat in Sahih Hadith, Mutawatir Qiraat in Dhaif ‘weak’ Hadith, Shath Qiraat in Sahih Hadith and Shath Qiraat in Daif Hadith.